PENERAPAN PERMAINAN LOMPAT CERIA UNTUK MENINGKATKAN KEMAMPUAN FISIK MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK PKK 3 GUNUNGSARI PASURUAN - Lailatul Magfiroh; Retno Tri Wulandari; Rosyidamayani Twinsari Maningtyas (Jurnal PAUD: Kajian Teori dan Praktik Pendidikan Anak Usia Dini, 2019)
Abstract: The purpose of this study was to describe the application of cheerful jumping games to improve the gross motoric abilities of early childhood in group B in Gunungsari PKK 3 Kindergarten and to describe the increase in gross physical motor skills of group B children in PKK 3 Gunungsari Kindergarten, Beji District, Pasuruan Regency through a cheerful jumping game. The research design used was classroom action research (CAR). This study was conducted in two cycles. Data collection techniques used were observation, interviews, and documentation. Analysis of the data used is qualitative and quantitative. Increasing gross motoric physical abilities of children from pre-action to the implementation of the second cycle with strength indicators increased by the percentage of 55,6%; balance increased by 77,7%; coordination increased by 77,8%; flexibility increased by 66,7%; and agility increased with a percentage of 66,7%; Based on the presentation of the results of the cheerful jumping game that the gross physical motor skills of children proved to be increasing